Navigating OCEAN Personality Theory in the Movie of Coco - Sapna, Aulia; Anjani, Atika (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
In this research, the major characters of Pixar’s Coco were analyzed using the approach of the Big Five or OCEAN (Openness, Conscientiousness, Extraversion, Agreeableness, Neuroticism) personality theory. This study seeks to determine how five personality dimensions show themselves in fictional characters based on the movie and how they shape narrative dynamics and cultural values of the movie. The method used is qualitative and works with content analysis in which there is a profound observation of behaviour, dialogue, and also emotions of characters. The results from the study showed that the most dominant dimension was Agreeableness which amounts to 33.33 percent reflecting Mexican character of being empathetic and compassionate and strong family harmony. Equal proportions of the other dimensions like Openness, Conscientiousness, Extraversion and Neuroticism appeared and all this depicted realistic character complexity and development. The results of this research proved that OCEAN theory could be an instrument to examine the psychological makeup of fictional characters and contributed to enlightening moral and cultural messages released in the movie.